Relationship between Husband Support and Childbirth Assistance during the 2019 Corona Virus Disease (COVID-19) Pandemic in Sekolaq Darat District - Siti Aisiyah Saragih; Wiyadi; Heni Suryani (Formosa Journal of Science and Technology, 2023)
This study aims to determine the relationship between husband's support and delivery assistance during the COVID-19 pandemic in Sekolaq Darat District. This type of research is an analytic survey with a cross sectional approach. The population in this study were all mothers giving birth from January to December 2021. Sampling in this study used the Purposive Sampling technique and a total of 64 respondents were obtained. Data collection was carried out by interviewing and using a questionnaire. The data analysis technique uses the chi square test to determine the relationship between variables. The results of the hypothesis test obtained a p-value of 0.00 (<0.05), so it can be concluded that there is a relationship between husband's support and delivery assistance during the COVID-19 pandemic in Sekolaq Darat District.